Peningkatan Kompetensi Guru Kimia Banjarmasin Utara: Pembelajaran Mendalam dengan Problem Based Learning Berbantuan Artificial Intelligence - Mahdian; Syarifah Meutiah Eka Sari; Iriani Bakti; Atiek Winarti; Ni Pt. Pande Mirah Surya Dewi (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2026)
Deep Learning is an approach that emphasizes creating meaningful, reflective, and enjoyable learning experiences. One appropriate learning method to support this approach is Problem-Based Learning (PBL). However, many high school chemistry teachers in North Banjarmasin are still unfamiliar with Deep Learning and have not yet implemented PBL optimally. Therefore, the solution offered is to conduct a workshop to improve chemistry teachers' understanding and skills related to Deep Learning and PBL. In this workshop, chemistry teachers were also provided with skills in using AI technology to facilitate the design of teaching materials that are in line with the Deep Learning and PBL approaches. To assess the results and impact of this activity on improving chemistry teachers' competencies, a pretest and posttest were used. Before the implementation, the average pretest score was recorded at 65 ± 23.21, indicating the diversity and limitations of chemistry teachers' knowledge. After the activity, the average posttest score increased to 96 ± 0.52. These results indicate that the workshop was effective and had a positive influence on improving chemistry teachers' abilities in implementing Deep Learning in PBL with the assistance of AI.